RBNCANA BISNIS MAKANAN MINUMAN ORGANIK POPAI - , Monica Helvi Mustika Dewi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Organic foods have many advantages among which is more nutritious than regular food. But this time the availability of organic food is still difficult to obtain freely. This is evident from the unavailability of organic foods in large quantities in the traditional market and is only available in supermarkets as well as to a particular lack of clear information that ensures the quality of organic products distributed in supermarkets. The availability of organic food in Indonesia is inversely proportional to the demand of the people who have started to realize the importance of organic food. Limited availability of healthy foods and the quality of organic food trend in the future is an opportunity for businesses to meet consumer demand for organic food availability. Trade of organic food is one form of trade in food and beverage industry. Food and beverage industry in Indonesia is a type of industry that continues to experience growth. Commodity foods and beverages is the primary commodity in the long term is needed by the community. Businesses in the sector of organic food and beverage industry is an opportunity. In order to capture these opportunities, POPAI presents a business unit that will offer innovative organic processed foods and beverages combined with organic fruits, so it can be easily consumed and acquired by consumers. Name of POPAI was chosen with the aim to bring the brand to consumers of POPAI organic food and beverage products. POPAI is one cartoon character who likes vegetables. In this effort, POPAI will offer innovative organic processed foods and beverages combined with organic fruits, so it can be easily consumed and acquired by consumers. POPAIâs business plan contains vision and mission to provide organic food and drinks. The vision and mission are based on the state of the scarcity of healthy food and beverages. POPAIâs business plan will be implemented in early 2014. Of the feasibility of investing, POPAI is a decent attempt to run. With initial investmen Rp.105.746.340, and price projections planned by Popai is Rp.6500, 00 with projected sales of Rp. 1.053.624 billion in one year, the total costs used in the operational within one year is Rp. 1.015.140.330, in order to obtain Rp.38.483.670 net income and cash flow from operations amounted to Rp. 45,699,920. From the calculation of cash flow from year to 0-5, obtained results of NPV is Rp. 54,990,847, this shows the investment project is acceptable since the NPV>1 so that the project will provide benefits and generate high returns. From the results of calculations performed by POPAI, it can be seen that the payback period will fall in the 27th month or two years three months.